2020
DOI: 10.1038/s42003-019-0715-9
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for detecting chaos in nature

Abstract: Chaos, or exponential sensitivity to small perturbations, appears everywhere in nature. Moreover, chaos is predicted to play diverse functional roles in living systems. A method for detecting chaos from empirical measurements should therefore be a key component of the biologist’s toolkit. But, classic chaos-detection tools are highly sensitive to measurement noise and break down for common edge cases, making it difficult to detect chaos in domains, like biology, where measurements are noisy. However, newer too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 95 publications
(209 reference statements)
3
112
0
Order By: Relevance
“…In this regard, we note that examining the NY daily death count data studied in Ref. Chin et al (2020) , these data are found to be characterized as stochastic rather than chaotic ( Toker, Sommer, & D’Esposito, 2000 ). Taleb seems to fit an unorthodox model, and then abandons all effort to predict anything.…”
Section: Further Thoughts – Analogies Decisions Of Action and Maximmentioning
confidence: 78%
“…In this regard, we note that examining the NY daily death count data studied in Ref. Chin et al (2020) , these data are found to be characterized as stochastic rather than chaotic ( Toker, Sommer, & D’Esposito, 2000 ). Taleb seems to fit an unorthodox model, and then abandons all effort to predict anything.…”
Section: Further Thoughts – Analogies Decisions Of Action and Maximmentioning
confidence: 78%
“…Chaos, which is the exponential sensitivity to small perturbations, is a ubiquitous phenomenon in nature [258,259]. Furthermore, chaos is related to how a deterministic dynamical system can be potentially unpredictable due to an extreme sensitivity to initial conditions, which is also known as the "Butterfly Effect" [259].…”
Section: Chaos Analysismentioning
confidence: 99%
“…When a single transcription factor, NF-kB, a well-described transcriptional regulator in cancer networks was modelled as a periodically forced nonlinear oscillator, chaotic dynamics emerged beyond a critical amplitude of TNF (Tumor Necrosis Factor) (Heltberg et al, 2019 [89]). Recently, these findings were confirmed with the Chaos Decision Tree algorithm, demonstrating the applicability of machine learning in detecting chaotic gene expression signals (Toker et al, 2020 [91]). Furthermore, chaotic behaviors are often equated with aperiodicity or disordered patterns of gene expression.…”
Section: Nonlinear Dynamics Fractals and Chaosmentioning
confidence: 85%